Application of the Factorial Design and Finite Element Methods to Optimize the Solidification of Cu-5wt%Zn Alloy in a Sand Mold - Pariona, M. M.; Salem, G. A.; Cheung, N. (Rev. Téc. Fac. Ing. Univ. Zulia)
In the study reported in this work, two-dimensional numerical simulations were accomplish for the solidification of the Cu-5 wt %Zn alloy in industrial greensand. The latent heat release during the solidification using different mathematical models was incorporated. In order to accomplish this work, the finite elements technique and the ANSYS software program were used. The thermo-physical properties of the alloy Cu-5 wt %Zn were considered temperature-dependent, while for sand were considered constant. In addition, a full three-level Box-Behnken factorial design has been employed in order to investigate the effect of the three factors on the casting process, namely initial temperature of the mold, the convection in the external mold and the latent heat release during the phase change. The results of the heat transfer shown throughout the 2D system, such as thermal flow, thermal gradient and the cooling curves at various points of the cast metal/mold were determined. It was verified that the mold temperature and the mathematical model of the latent heat realease are the most important parameters in the solidification process.